2014
DOI: 10.2147/dddt.s58803
|View full text |Cite
|
Sign up to set email alerts
|

Combined isosorbide dinitrate and ibuprofen as a novel therapy for muscular dystrophies: evidence from Phase I studies in healthy volunteers

Abstract: We designed two Phase I studies that assessed healthy volunteers in order to evaluate the safety and to optimize the dosing of the combination of the drugs isosorbide dinitrate, a nitric oxide donor, and ibuprofen, a nonsteroidal antiinflammatory drug. We designed these studies with the aim of designing a Phase II trial to evaluate the drugs’ efficacy in patients affected by Duchenne muscular dystrophy. For the first trial, ISOFEN1, a single-dose, randomized-sequence, open-label, active control, three-treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In addition the combination of a non-steroidal anti-inflammatory drug, ibuprofen, and an NO donor, isosorbide dinitrate, were capable of preventing morphological changes in the heart of mdx mice [105]. A recent phase 1 clinical trial using this combinatory therapy, demonstrated an excellent safety profile in healthy patients [106]. This provides a solid basis for further trials in muscular dystrophy patients.…”
Section: Current Clinical Disease Management and Application Of Comentioning
confidence: 99%
“…In addition the combination of a non-steroidal anti-inflammatory drug, ibuprofen, and an NO donor, isosorbide dinitrate, were capable of preventing morphological changes in the heart of mdx mice [105]. A recent phase 1 clinical trial using this combinatory therapy, demonstrated an excellent safety profile in healthy patients [106]. This provides a solid basis for further trials in muscular dystrophy patients.…”
Section: Current Clinical Disease Management and Application Of Comentioning
confidence: 99%
“…The importance of NO in muscle repair also emerges from the observation that nNOS signalling is defective in many genetically diverse skeletal muscle diseases in which muscle repair is dysregulated, including Duchenne muscular dystrophy, Becker muscular dystrophy, limb-girdle muscular dystrophies 2C, 2D and 2E, Ullrich congenital muscular dystrophy and inflammatory myositis [ 3 , 10 - 13 ]. Based on this evidence and on the fact that the restoration of NO signalling by nNOS overexpression ameliorates muscle function [ 14 , 15 ], genetic and pharmacologic strategies to boost nNOS/NO signalling in dystrophic muscle are being tested with encouraging results: in particular, the combination of NO donation with non steroidal anti-inflammatory activity limits muscle damage and favours muscle healing in vivo [ 16 - 18 ] such that it is currently being tested as a therapeutic for Duchenne muscular dystrophy in humans [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of ibuprofen did not show good results related to the immune system, where the ingestion of drinks with carbohydrates during intense and prolonged exercises attenuated the increase in plasma cytokines and stress hormones, superior to the use of ibuprofen, however, partially limited [ 64 ]. The use of ibuprofen alone or in combination with other drugs in patients affected by Duchenne muscular dystrophy, being evaluated in maximum concentration, did not affect these indicators [ 65 ]. Yet another study that evaluated the influence of ibuprofen use on hypertrophy showed that ibuprofen presented a reduction in inflammation-induced muscle weakness.…”
Section: Discussionmentioning
confidence: 99%